PENGARUH MODAL KERJA DAN PENGGUNAAN APLIKASI E-COMMERCE (SHOPTIMIZE) TERHADAP PENDAPATAN UMKM DI KOTA MEDAN - Muhammad Yafiz, Mawaddah Irham, Yenti Agustina Br Purba, (Islamic Circle, 2021)
This type of research is quantitative research. The population in this study are Muslim MSME actors who use the Shoptimze application in the city of Medan. The sample in this study was 75 respondents. The results showed that: 1) Working capital had a significant effect on the income of Muslim SMEs in the city of Medan with a positive regression coefficient of 0.381 or 38.1% and the value of t count > t table that was 3.529 > 1,666. 2) The e-commerce application (Shoptimize) has a significant effect on the income of Muslim MSME actors in the city of Medan with a positive regression coefficient of 0.513 or 51.3% and the value of t arithmetic > t table which is 5.083 > 1.666. 3) Working capital and shoptimize applications have a simultaneous effect on the income of Muslim MSMEs in the city of Medan. The result of the coefficient of determination (R2) is a coefficient value of 0.593 in other words the effect of working capital and the use of Shoptimize on the income of Muslim MSME actors is 0.593 or 59.3% while the rest i40.7% is influenced or can be explained by other variables such as the effect of length of business, market, location, and working hours.